Faculty Benefits From Medical Student Learning Communities: A Junior and Senior Faculty Members' Perspectives. (February 2019) - Ngo, Thuy L; Whipple, Mark
Medical school learning communities have many benefits for students. In this perspective, the authors briefly describe how learning communities have benefited them as faculty. These include finding other like-minded faculty, improving communication and clinical skills, career advancement through scholarly work associated with the learning community, and above all, developing mutually beneficial relationships with students. Here, they offer viewpoints from junior and senior faculty members on how the learning community has positively affected them.